The impact of the global COVID-19 pandemic exposure on current and future worldwide environmental protection across 18 nations in 6 continents - Chao Guo; Huameng Tang; Mingxing Wang; Tingting Zhang (Global Transitions)
Objectives: Amid the challenges posed by the global COVID-19 pandemic, understanding how the crisis shapes people' environmental behaviours and consciousness becomes paramount. This study aimed to unravel the implications of the global pandemic on individuals' environmental protection activities, environmentally prioritized attitudes, and confidence in future environmental protection movements. Methods: By combing detailed COVID-19 surveillance data from the World Health Organization and the Integrated Values Surveys, this study analysed information from 54,951 participants aged 15 years and above across 18 countries spanning 6 continents. Utilizing the global pandemic as a natural experiment, Logistic regressions with Difference-in-Difference (DID) models were employed for a robust estimation of the pandemic's effects on environmental outcomes. Results: The findings revealed a notable reduction in the likelihood of environmental protection activities among individuals (adjusted OR: 0.34, 95% CI: 0.23–0.51). However, pandemic exposure was linked to an increased environmentally prioritized attitude (1.35, 1.18–1.54) and enhanced confidence in environmental protection movements (1.16, 1.01–1.32). Notably, the beneficial effects of the pandemic on environmental attitudes (1.42, 1.21–1.67) and confidence (1.19, 1.01–1.39) were significantly observed exclusively among younger individuals and women exhibited heightened sensitivity to the pandemic's positive impact on environmental attitudes (1.55, 1.30–1.86), while men displayed increased sensitivity in confidence regarding future environmental movements (1.23, 1.00–1.50). Conclusions: This study contributes valuable insights to the existing literature by elucidating the intricate relationship between global crises and individual environmental protection. The evidence generated provides policymakers with essential information for formulating comprehensive post-pandemic strategies aimed at jointly promoting and achieving high-quality development of the population and the environmental dimension of SDGs.